An Update on Phytochemicals and Pharmacological Activities of the Genus Persicaria and Polygonum - Seimandi, Gisela Marisol (2021)
The discovery of new pharmaceutical identities, particularly anti-infective agents, rep-resents an urgent need due to the increase in immunocompromised patients and the ineffective-ness/toxicity of the drugs currently used. The scientific community has recognized in the last decades the importance of the plant kingdom as a huge source of novel molecules which could act against different type of infections or illness. However, the great diversity of plant species makes it difficult to select them with probabilities of success, adding to the fact that existing information is difficult to find, it is atomized or disordered. Persicaria and Polygonum constitute two of the main representatives of the Polygonaceae family, which have been extensively used in traditional medicine worldwide. Important and structurally diverse bioactive compounds have been isolated from these genera of wild plants; among them, sesquiterpenes and flavonoids should be remarked. In this article, we firstly mention all the species reported with pharmacological use and their geographical distribution. Moreover, a number of tables which summarize an update detailing the type of natural product (extract or isolated compound), applied doses, displayed bioassays and the results obtained for the main bioactivities of these genera cited in the literature during the past 40 years. Antimicrobial, antioxidant, analgesic and anti-inflammatory, antinociceptive, anticancer, antiviral, antiparasitic, anti-diabetic, antipyretic, hepatoprotective, diuretic, gastroprotective and neuropharmacological activities were explored and reviewed in this work, concluding that both genera could be the source for upcoming molecules to treat different human diseases.